Prevalence of Neonatal Convulsion in Yemeni Children -A Hospital Based Study - Sallam, AbdulKhaliq Ali; Al-Selwi, Abdulhakim Ali; Albahlooly, Mohamed Abdulhadi (Journal of medical and pharmaceutical sciences, 2018)
Background: Seizure is a common neurological problem in small children, mainly seen at neonatal period. Neonatal seizures have always been a topic of interest because of their universal occurrence. It contributes significantly to neonates morbidity and mortality particularly in developing countries including Yemen. A varied number of conditions are capable of causing seizures in the neonatal period. Objectives: study to determine the pattern, incidence and outcome of neonatal seizures. Design: A prospective Descriptive study. Setting: Pediatric unit, AL Salam Hospital (PUAH), Sadah, Yemen. Subjects: All newborn infants with observed seizures admitted between July 2013 - Aug 2015. Methods: A Hospital based prospective observational study was undertaken in the Pediatric unit AL Salam Hospital (PUAH) over two years period(July 2013 - Aug 2015) , All neonates < 28 days of life with observing of abnormal movements ( seizures) were admitted in this unit. Detailed antenatal, natal and postnatal history was taken and examination of baby was done. Then, relevant investigations including biochemical parameters were done. Data were analyzed using SSPS for Windows version 10. Results: Of 1732 admitted neonates 62.6% were males and 37.4% were females. The incidence of neonatal seizures in this pediatric unit was 68 per 1,000 admissions. Out Of 1732 neonates admitted, 118 (6.8%) had seizures; of these 86 (72.9%) had been born outside hospital (out-born). The incidence of neonatal seizures in Pediatric unit, AL Salam Hospital (PUAH) with seizures had a higher birth weight than babies without seizures (p=0.008), Of 118 babies with seizures, 74 (62.7%) were considered to have had birth asphyxia, 14(11.9%) Meningitis, 12(10.2%) hypoglycemia, 4(3.4%) hypocalcaemia and 14 (11.9%) had undiagnosed causes. Eighty Four (71.2%) of the 118 babies had both subtle and generalized seizures. Fifty Four babies with seizures died (45.8%) compared with 262 of 1614 babies without seizures (16.2%, p=0.0001). Babies with seizures and asphyxia or who had been out born had the highest risk of death (59.5% and 48.8%, respectively). Conclusion: Birth asphyxia was the main cause of babies with seizures. All seizures in the first 24 hours of life were associated with asphyxia. Seizures following infection tended to occur at any age after 24 hours of life. Major presentation of babies with seizures were both subtle and generalized seizures. The higher mortality rate among asphyxiated babies had seizures compared with those without seizures. Babies born outside this hospital had a higher mortality rate than those inborn babies.